The Influencing Factors Affecting Low-Code Technology Adoption: A Case Study of the Small and Medium-Sized Advertising Agencies in China - Jingchuan, Yang; Wongkumchai, Tachakorn; Chaiwiwat, Uswin; Soprakan, Chulalux (Administrative Journal for Local Development, 2024)
Low-code development platforms (LCDPs) were transforming software development by enabling individuals with limited coding skills to create applications. This was particularly relevant for Small and Medium-Sized Advertising Agencies (SMAs) striving for efficiency, agility, and digital innovation in a competitive market. However, the adoption of LCDPs in SMAs was influenced by various technological, organizational, and economic factors. This study aimed to identify the key factors influencing the adoption of LCDPs in SMAs and provide practical guidance for their implementation. A mixed-methods approach was employed, incorporating both quantitative and qualitative research methods. Data were collected from 112 respondents, comprising IT developers and non-IT personnel in SMAs, through a questionnaire and in-depth interviews. Multiple linear regression analysis was conducted to determine the significant predictors of LCDP adoption. The results revealed that cost considerations (β = 0.211) and perceived security risks (β = 0.260) emerged as the most significant factors influencing LCDP adoption in SMAs. While perceived efficiency, ease of use, and reduced IT dependency were also contributing factors, their influence was less pronounced than cost and security concerns. The study concluded that SMAs were increasingly recognizing the potential of LCDPs to enhance digital innovation and operational efficiency. However, successful adoption hinged on addressing economic factors, such as providing affordable pricing models, and fostering trust by prioritizing robust security features and transparent communication about data protection. These findings provided valuable insights for LCDP providers and SMAs, guiding the development and implementation of these platforms to maximize their potential in the dynamic advertising industry.